The state of free-radical processes and antioxidant protection system at brain gliomas in clinic and experiment - Rozumenko, V. D.; Sutkovoy, D. A.; Troyan, O. I.; Dmitrenko, A. B.; Makarova, T. A. (Ukrainian Neurosurgical Journal, 2008)
Recent data of literature, which have shown that development of brain tumors is tightly connected with pro- and antioxidant status destabilization at patient’s organism. The purpose of our research was to study state of free-radical processes and antioxidant protection (AOP) system in blood of patients with malignant brain tumors; and to research the activity of lipid peroxidation process (LPP) and AOP system in brain and blood of experimental animals, which underwent the transplantation of glioma’s A-101.8. In blood of patients with brain tumors the LPP activity increases while the activity of AOP system enzymes decreases. Experimental researches have revealed the cross-correlation connection of LPP destabilization processes in the brain and blood of animals and tumor growth intensity, followed the implantation of glioma A-101.8. The reliable increase of LPP activity in the brain of experimental animals has been demonstrated while the activity of AOP system was depressed.